Influencing factors and gaps of blood donation knowledge among university and college students in Myanmar: a cross-sectional study - Pramon Viwattanakulvanid; Aye Chan Oo (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Blood donation knowledge of healthy young students is crucial to donate blood voluntarily and regularly in long-term. This study aimed to determine the influencing factors on the blood donation knowledge, to identify gaps of blood donation knowledge and reasons for not donating blood among university and college students in Yangon, Myanmar. Design/methodology/approach - Cross-section survey (May 2019) was conducted in students of Yangon Technological University (YTU) and National Management Degree College (NMDC) with the use of quota and convenience sampling method. The questionnaires covered sociodemographic characteristics, blood donation knowledge and reasons for not donating blood. Findings - Total 320 students (129 males and 191 females) with age of 18 to 23 years old participated. Previous blood donation had statistically significant influence on blood donation knowledge scores (ß = 0.396, p < 0.001). Gaps of knowledge between nondonors and blood donors were recorded, especially in universal recipient blood groups, Rh blood groups, blood donation interval, eligibility criteria, transfusion-transmitted infections (TTIs), amount of blood removed in donation, benefits of blood donations and misbelief of infections from blood donation. Top three reasons for not donating blood among nondonors were (1) no opportunity, (2) fear to donate and (3) still underage to donate. Originality/value - Blood donations programs should extend awareness-raising programs in academic society and population at large. Raising awareness should focus on the knowledge gaps such as donor eligibility, interval of blood donations, TTIs and benefits of donating blood to recipients.